THE EFFECT OF COLLABORATIVE WRITING TECHNIQUE ON STUDENTS WRITING ABILITY AT THE EIGHTH GRADE OF SMP NEGERI 8 PEMATANGSIANTAR - Mardin Silalahi; Nelma Hartati Simamora (Program Studi Pendidikan Bahasa Inggris FKIP, 2019)
Writing is the difficult skill to master that is why exercise regularly is needed. The objective of this study is to figure out the improvement on students to write descriptive through collaborative writing technique. This experimental research was carried out in SMP Negeri 8 Pematangsiantar in the academic year of 2019/2020. The research design of this study is classroom action research with quantitative approach. The population of this study is all students grade eight at junior high school, they are 296 students were divided into ten classes. And as a sample of this study consist of 25% from the population were VIII-4 as the experimental group and VIII-7 as the control group. Each group consists of 32 students. The experimental group was treated by using Collaborative Writing Technique, while the control group was treated by using Direct Instruction. The finding of this research are the score pre-test in control group are 1376 where the mean is 43 and in experimental group 1529 where the mean is 47.78. The mean score of different in control group is 23.21. and the t-test is 5.10. The standard deviation of the data in control group is 11.70 and the effect size in teaching writing descriptive text in control group is 1.98. It means that the students ability is low. The students’ score post-test in control group are 2119 where the mean is 66.21 and in experimental group are 2409 where the mean is 75.28. The mean score of different in experimental group is 27.5 and t-test for experimental group is 5.27. The standard deviation of the data in experimental group is 13.29 and the effect size in experimental group is 2.35. It means that the students ability is high.The data analysis shows the following findings: (1) Collaborative Writing Technique is more effective than Direct Instruction in teaching writing; (2) students with high creativity have better writing ability than those having low creativity; (3) there is an interaction between teaching techniques and creativity in teaching writing.